Effect Size of STEM-Based Problem Based Learning Model on Problem Solving Ability in Students - Munir Tubagus; Ichsan Ichsan; suhaimi Suhaimi; Abdul Rahman; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effect size of the STEM-based problem-based learning model on students' problem-solving skills. This type of research is a meta-analysis. Data sources come from 14 national and international journals. The process of finding sources in research through Google Scholar. Eric and ScienceDirect. Data collection techniques are direct observation and documentation tracing the journal database. Data analysis is quantitative statistical analysis with the help of the Comprehensive Meta-Analysis (CMA) veris 3.0 application. The results showed that the average effect size value of 0.912 was high. This finding shows that there is a significant effect of the STEM-based problem-based learning model on students' problem-solving skills. The problem-based learning model helps students think at a higher level in learning